Research progress on functional tic-like behaviors - QIAO Fu-qiang; XU Ke-ying; WANG Lei (Chinese Journal of Contemporary Neurology and Neurosurgery, 2025)
Functional tic-like behaviors (FTLBs) is a kind of rare clinical phenotype of functional neurological disorder (FND), its etiology and pathogenesis have not been fully defined, and the clinical understanding of it is not comprehensive. This paper systematically reviews the relevant studies of FTLBs in recent years, and analyzes and summarizes its clinical characteristics, influencing factors, comorbidities, diagnosis, treatment and prognosis, aiming to provide theoretical reference for the subsequent diagnosis and treatment of FTLBs.